PentaRay Catheter in Persistent Atrial Fibrillation Ablation - Teixeira, P (2016)
Submitted by Ana Quininha (ana.quininha@chlc.min-saude.pt) on 2016-03-24T16:34:08Z No. of bitstreams: 1 RPC 2016 121.pdf: 975113 bytes, checksum: 9a5c6b30b0f3fb32d34d9a34d4d13ba1 (MD5)